TECHNOLOGY ELEMENTS WITH IMPLICATIONS UPON SEED PRODUCTION OF THE „ARIESAN’’AUTUMN WHEAT VARIETY - Monica, Cetean (University of Cluj-Napoca Agricultural Sciences and Veterinary Medicine, Romania, 2018)
The seed production potential can be improved a lot by applying an optimal technology of growing, starting by locating the seed lot after a good, and wellbalanced forerunner fertilization, disease control, weed control, pest, harvesting the ripe, a right storage.